STORYTELLING METHOD TO IMPROVE MOTIVATION IN LEARNING ISLAMIC RELIGIOUS EDUCATION - Idharudin, Abdul Jabar; Nurhasanah, Muwahidah; Rahman; Arsyadi, Isrofil Mirajul (INTIHA: Islamic Education Journal, 2026)
This research arises from the significance of effective educational approaches in improving students' engagement, especially in Islamic Education at SDIT AL-Hidayah Bogor. This research aims to create and implement storytelling techniques as a learning method that could enhance students' engagement. The research method used is a qualitative case study, with data collection through observation, interviews, and documentation related to the application of storytelling methods in the school. The study results indicate that the storytelling method applied holistically through religious teaching with the subject "Stories of Righteous Children," as well as integration with the school's literacy program and student cultural presentations, has proven effective in enhancing student motivation. Additionally, regular training for educators and school community members also contributes to the successful implementation of this method. This research identifies challenges, including the conventional nature of storytelling methods, the lack of relevant context, and limitations in technology integration. Therefore, this study offers solutions by using more varied and contextual methods and utilizing digital media to enhance the appeal of learning. The novelty of this research lies in integrating storytelling methods within a broader context of religious education and emphasizing the importance of adapting technology in the learning process.